Crises and women’s access to agricultural information: Insights from India and Nepal during the COVID-19 pandemic - Alvi, Muzna; Barooah, Prapti; Gupta, Shweta; Saini, Smriti (International Food Policy Research Institute, 2023)
Strict lockdown measures implemented in response to the COVID-19 pandemic had extensive impacts on agriculture, and especially on women farmers. These effects were worsened by a lack of reliable and timely access to agricultural extension. This note summarizes findings from panel phone surveys conducted in India and Nepal on the impacts of lockdown measures on women's ability to access agricultural extension services and their perceived impact on agricultural productivity. We find that women's already limited access to formal extension services was further reduced during the pandemic, leading to greater reliance on informal social networks. In both countries, approximately 50 percent of farmers reported negative consequences on productivity due to the unavailability of information during the lockdown. We propose strategies to enhance the inclusivity and resilience of extension systems in India and Nepal in future crises, including through the use of group- and community-based approaches.